Assessment of information delivery systems used for dissemination of HIV/AIDS information by selected clinics at Ga-Molepo, Capricorn District in the Limpopo Province - Dikotla, Maoka Andries (My University, 2008)
The aim of the study is to investigate which of the information delivery systems (communication strategies) established at government level are used by rural clinics, and whether such information delivery systems are accessible to rural end-users. A literature review discussing and assessing the use of information delivery systems was conducted. The survey method and semi-structured interviews were used to collect data from all Clinics at Ga- Molepo. The study revealed that rural end-users cannot access HIV/AIDS information because clinics use information delivery systems which are not acceptable and accessible to them. Recommendations for further study on the subject under investigation are provided. The study assumes that with the identified barriers and recommendations at their disposal HIV/AIDS campaigners will be in a good position to identify, package and employ information delivery systems which are suitable for end-users.
Thesis (M.Inf.) --University of Limpopo, 2008
Keywords: Information needs; Information sources; 025.52; Information Services -- South Africa -- Limpopo; Selective dissemination of information